Early Detection Of Currency Crisis In Indonesia Based On Jci Indicator Using A Combination Of Volatility And Markov Switching Models - Berlyana Ayu Prasasti; Sugiyanto Sugiyanto; Sri Subanti (Publikasi Indonesia, 2023)
Currency crises have occurred in Indonesia in 1997-1998 and 2008, causing significant losses both in terms of economy and social life. Therefore, a system is needed that can detect currency crises to create economic and currency stability. Crises can be detected through economic indicators such as Indonesia Stock Exchange Composite Index (IDX Composite) or Jakarta Composite Index (JCI). This study aims to determine the appropriate model and to predict the currency crisis in Indonesia from November 2022 to October 2023 based on the JCI indicator. The study begins by forming an AR model, then a volatility model in the form of an ARCH model, and finally a combined volatility model and Markov switching two-state model. This combined model is then used to form a smoothed probability that can detect crises. The results of the study indicate that the MS-ARCH(2,1) model is the appropriate model, and from the detection results, it is found that Indonesia will not experience a currency crisis from November 2022 to October 2023.